2015
DOI: 10.1038/ncomms7681
|View full text |Cite
|
Sign up to set email alerts
|

Crossreactivity to vinculin and microbes provides a molecular basis for HLA-based protection against rheumatoid arthritis

Abstract: The HLA locus is the strongest risk factor for anti-citrullinated protein antibody (ACPA) þ rheumatoid arthritis (RA). Despite considerable efforts in the last 35 years, this association is poorly understood. Here we identify (citrullinated) vinculin, present in the joints of ACPA þ RA patients, as an autoantigen targeted by ACPA and CD4 þ T cells. These T cells recognize an epitope with the core sequence DERAA, which is also found in many microbes and in protective HLA-DRB1*13 molecules, presented by predispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 62 publications
1
68
0
3
Order By: Relevance
“…10 and Supplementary Tables 20 and 21). Thus, both the gut and the oral microbiome might contribute to RA through molecular mimicry of self-antigens 34,35 .…”
Section: Concordance Between Gut and Oral Microbiomesmentioning
confidence: 98%
“…10 and Supplementary Tables 20 and 21). Thus, both the gut and the oral microbiome might contribute to RA through molecular mimicry of self-antigens 34,35 .…”
Section: Concordance Between Gut and Oral Microbiomesmentioning
confidence: 98%
“…A recent study revealed that the citrullinated DERAA motif, which was found in the protective DRB1 allele products, including DRB1*13 protein, and in vinculin, can be presented by the DQ proteins that were encoded on the RA susceptible DR-DQ haplotypes. 20 The protective effect of DRB1*13 against RA was explained by the cross-reactivity of self-reactive T cells to the citrullinated DERAA motif in vinculin and DRB1*13 protein, and the absence of these self-reactive T cells in the DR4/DR13 heterozygotes. 20 Self-peptides that are derived from other potential self-antigens, including type II collagen and nuclear ribonucleoprotein A2 can also be presented to the susceptible DR or DQ allele products and are involved in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…20 The protective effect of DRB1*13 against RA was explained by the cross-reactivity of self-reactive T cells to the citrullinated DERAA motif in vinculin and DRB1*13 protein, and the absence of these self-reactive T cells in the DR4/DR13 heterozygotes. 20 Self-peptides that are derived from other potential self-antigens, including type II collagen and nuclear ribonucleoprotein A2 can also be presented to the susceptible DR or DQ allele products and are involved in the pathogenesis of RA. [21][22][23][24][25] The binding affinity of DR4 with class II-associated invariant chain peptide (CLIP) may also affect RA risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Высказано предположение, что HLA-DRB1*13 участвует не в «презен-тации» аутоантигенов, а в делеции в тимусе Т-клеток, об-ладающих перекрестной реактивностью с антигенами ми-кроорганизмов и аутоантигенами [177].…”
Section: генетические фак торыunclassified